Edukasi Bahaya Formalin, Cara Identifikasi dan Upaya Penurunan Risiko pada Produk Pangan di MAN 3 Pontianak - Dermawan, Abdurraafi' Maududi; Dwisari, Fath; Jumadilah, Rahmi; Tjoadri, Tessa Nathalia (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
The use of formalin as a food additive is prohibited according to Indonesian Minister of Health Regulation No. 033 of 2012 concerning Food Additives (BTP). Due to its easy availability and its ability to extend shelf life, formalin is often misused as a food preservative. Given its carcinogenic properties, the use of formalin in food poses health risks. The purpose of this community service is to provide education on the dangers of formalin, identification techniques for formalin, and de-formalization efforts in food products. The community service was conducted on July 25, 2024, with 30 students from MAN 3 Pontianak participating. The service was carried out using an outreach method at MAN 3 Pontianak, including pre-tests, material delivery, demonstrations, and post-tests. The results from the pre-test and post-test show an average knowledge increase of 19% regarding formalin risks and reduction efforts. Following the education through material presentation and demonstrations, the number of students with good knowledge increased to 26 (86.7%), while those with insufficient knowledge decreased to 4 (13.3%). The attitude assessment revealed that all students at MAN 3 Pontianak had a positive attitude towards the dangers of formalin and efforts to reduce formalin risks in food (100%).